Down syndrome with primary thyroid diffuse large B-cell lymphoma and Hashimoto thyroiditis: A CARE compliant case report. Issue 35 (August 2019) - Wei, Luyang; Zhao, Ning; Li, Yalun; Zheng, Xiaodan; Zhang, Huaxin; Zhang, Zhongtao
Abstract: Rationale: Adult patients with Down syndrome (DS) commonly develop Hashimoto thyroiditis (HT). However, primary diffuse large B-cell lymphoma (DLBCL) of the thyroid is uncommon, and its simultaneous occurrence with HT is very rare. To our knowledge, coexisting DLBCL and HT in a patient with DS has not been reported in the medical literature. Patient concerns: We present a 43-year-old woman with DS who reported progressive swelling of the neck on the right side and dyspnea over the previous 1 month, with associated neck ache, hoarseness, and dysphagia. Thyroid ultrasonography and computed tomography of the neck revealed a large mass in the right lobe compressing the surrounding tissues. Diagnoses: Based on the clinical and histopathologic findings, the patient was diagnosed with coexisting primary thyroid DLBCL and HT. Interventions: A palliative unilateral thyroidectomy was performed; postoperative histopathology and immunohistochemistry revealed thyroid DLBCL and HT. The patient was scheduled for chemotherapy and targeted therapy after recovering from surgery. Outcomes: The patient died 3 weeks after surgery due to asphyxia caused by uncontrollable growth of recurrent tumor. Lessons: The coexistence of DS, primary thyroid DLBCL, and HT is very rare. There is no standardized approach to the clinical identification of primary thyroid lymphoma (PTL), making early diagnosis difficult. A multidisciplinary approach and close follow-up are needed. The mechanisms of the link between DS and PTL are poorly understood and remain to be elucidated.